Implementation Of The Storytelling Method - Rahman, Ikhwan; Yepi, Elma; Zeky, Serpuadi; Mutathahirin, Mutathahirin (Journal of Islamic Early Childhood Education, 2025)
This study aims to describe teachers' efforts to improve the self-confidence of early childhood through storytelling methods at TK IT Ar Rahmah Plus Al Qur'an. The background of this study is based on the continued discovery of children who lack self-confidence, have difficulty communicating and interacting socially, and limited teacher creativity in implementing interesting learning methods. This study used a qualitative approach with descriptive methods. Data were collected through observation, interviews, and documentation with informants consisting of one class teacher and the principal, as well as research subjects of 22 students. Data analysis was carried out through the stages of data reduction, data presentation, and drawing conclusions. The learning process using the storytelling method includes three main stages: initial activities, core activities (pre-, during, and post-storytelling), and closing activities. The results of the study indicate that the storytelling method is effective in improving children's self-confidence. Improvements are seen when children begin to dare to speak in front of the class, answer teacher questions, and retell the story with increased expression and enthusiasm. Storytelling activities encourage children to express themselves, communicate verbally, and interact with peers more confidently. Thus, the storytelling method has proven to be an effective learning strategy in fostering self-confidence in early childhood.